A distinguishing feature of Pongo upper molars and its implications for the taxonomic identification of isolated hominid teeth from the Pleistocene of Asia. Issue 4 (25th October 2019) - Ortiz, Alejandra; Bailey, Shara E.; Delgado, Miguel; Zanolli, Clément; Demeter, Fabrice; Bacon, Anne‐Marie; Nguyen, Thi M. H.; Nguyen, Anh T.; Zhang, Yingqi; Harrison, Terry; Hublin, Jean‐Jacques; Skinner, Matthew M.
Abstract: Objectives: The taxonomic status of isolated hominoid teeth from the Asian Pleistocene has long been controversial due to difficulties distinguishing between pongine and hominin molars given their high degree of morphometrical variation and overlap. Here, we combine nonmetric and geometric morphometric data to document a dental pattern that appears to be taxonomically diagnostic among Pongo . We focus on the protoconule, a cuspule of well‐documented evolutionary history, as well as on shape differences of the mesial fovea of the upper molars. Materials and methods: We examined 469 upper molars of eight hominid genera ( Australopithecus, Paranthropus, Homo, Meganthropus, Sivapithecus, Pan, Gorilla, and Pongo ), including representatives of Homo erectus and extinct and recent Pongo . Analyses were conducted at the enamel‐dentine junction to overcome the limitations introduced by dental wear. Results: We found that a moderate or large protoconule is present in ~80% of Pleistocene and extant Pongo . Conversely, a moderate to pronounced protoconule in hominins, Meganthropus, and African great apes occurs in low frequencies (~0–20%). Canonical variate analyses for the mesial fovea show that Pleistocene and extant Pongo cluster together and are clearly differentiated from all other groups, except for Sivapithecus . Discussion: This study suggests that the protoconule and the shape of the mesial fovea in upper molars are useful features for the taxonomic identification of isolated hominid teeth. By identifying these new features, our results can contribute to the better understanding of hominoid evolutionary history and biogeography during the Asian Pleistocene. However, we emphasize that the reported features should be used in combination with other diagnostic variables for the most accurate taxonomic assessments.